School counseling in the digital ERA: Empowering empathy through psychosocial guidance and educational technology integration - Susilawati, Heny; Sugiharto, DYP.; Sunawan, Sunawan; Mugiarso, Heru (Edelweiss Applied Science and Technology, 2025)
Nursing education in Indonesia continues to expand, particularly at the vocational level, where students are trained in both clinical and non-clinical skills. Empathy and self-esteem are essential psychological traits that support nurses in providing high-quality care and maintaining emotional stability. While self-esteem was once viewed as a static trait, current understanding recognizes it as dynamic and influential in shaping identity, motivation, and mental well-being. Religiosity and social support play significant roles in enhancing emotional regulation, reducing aggression, and fostering empathy among nursing students. This study aims to explore the influence of religiosity, social support, and self-esteem on the empathy levels of vocational nursing students. Employing a quantitative descriptive approach, the research utilized adapted questionnaires to measure the variables of religiosity, social support, self-esteem, and empathy. Data analysis involved descriptive statistics and Structural Equation Modeling with Partial Least Squares (SEM-PLS) to assess the relationships among variables and test the proposed hypotheses. The results support all hypotheses, indicating that religiosity, social support, and self-esteem each positively influence empathy. Religiosity has a modest but positive impact, functioning mainly as a supplementary factor in developing empathic behavior. Social support demonstrates a stronger influence by promoting emotional connection and a sense of belonging. Self-esteem emerges as the most significant factor, substantially enhancing emotional responsiveness and empathy. Collectively, these three variables explain 56.7% of the variance in empathy, underscoring the importance of internal psychological traits and social factors in fostering empathy among nursing students. The findings highlight the need for educational strategies that strengthen self-esteem, social support networks, and spiritual engagement to cultivate more empathetic healthcare professionals.